Mindfulness Concept for Happiness in Life - Hermawan Hermawan; Julia Surya; Ponijan Ponijan (Journal of Education Technology Information Social Sciences and Health, 2024)
This research discusses the concept of mindfulness for life happiness. Mindfulness, as a form of meditation that focuses on the present moment, is believed to be able to transform perceptions and responses to life experiences. The importance of neurobiological aspects in relation to mindfulness is also highlighted in scientific literature. Neuroscience research indicates that mindfulness practices can influence the structure and function of the brain, particularly in areas involved in emotional regulation and attention. The research methodology applied in this study is a systematic literature review (SLR) to collect and analyze relevant articles. The findings show that mindfulness practices can positively contribute to individual happiness, with happiness considered a central aspect of psychological well-being. The contribution of mindfulness to psychological well-being emphasizes its potential to enhance individual happiness, taking into account neurobiological aspects, stress management, individual variability, and ethical considerations.